Mendelian randomization study on the causal relationship between food and cholelithiasis - Liu, Zhicheng; Liu, Shun; Song, Peizhe; Jiao, Yan (Frontiers in Nutrition, 2024)
Background: Cholelithiasis, commonly referred to as gallstones, is a prevalent medical condition influenced by a combination of genetic factors, lifestyle choices, and dietary habits. Specific food items have been associated with an increased susceptibility to cholelithiasis, whereas others seem to offer a protective effect against its development.Methods: In this study, we conducted a Mendelian randomization (MR) analysis using a large-scale genetic dataset comprising individuals with European ancestry to explore the potential causal relationship between diet and cholelithiasis. The analysis incorporated 17 food-related variables, which were considered as potential factors influencing the occurrence of this condition.Results: Our findings indicate that a higher consumption of cooked vegetables, dried fruit, and oily fish is associated with a reduced risk of cholelithiasis. Conversely, a higher consumption of lamb is associated with an increased risk of developing the condition. Importantly, these associations proved robust to sensitivity and heterogeneity tests, and the pleiotropic test results further supported the hypothesis of a causal relationship between diet and cholelithiasis.Conclusion: Through our study, we provide compelling evidence for the existence of a causal relationship between diet and cholelithiasis. Adopting a dietary pattern enriched with cooked vegetables, dried fruit, and oily fish, while minimizing lamb intake, may contribute to the prevention of cholelithiasis. Recognizing diet as a modifiable risk factor in the prevention and management of this condition is of paramount importance, and our study offers valuable insights in this regard.